2015
DOI: 10.1007/s10571-015-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

The Edible Red Alga Porphyra yezoensis Promotes Neuronal Survival and Cytoarchitecture in Primary Hippocampal Neurons

Abstract: The edible red alga Porphyra yezoensis is among the most popular marine algae and is of economic and medicinal importance. In the present study, the neurotrophic and neuroprotective activities of the ethanol extract of P. yezoensis (PYE) were investigated in primary cultures of hippocampal neurons. Results revealed that PYE significantly increased neurite outgrowth at an optimal concentration of 15 µg/mL. PYE dose-dependently increased viable cells, significantly accelerated the rate of neuronal differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…PYEDE treatment can effectively inhibit the activity of iNOS, reduce the content of NO and alleviate damage to the hippocampus and brain atrophy, possibly by renewing the ability of the brain to scavenge ROS (in vitro) and reducing lipid peroxidation and protein carbonylation. Previous studies have shown that inhibition of iNOS and NO generation can attenuate hippocampal neuronal apoptosis, and an ethanol extract of P. yezoensis promoted the development of hippocampal neurons by enhancing the rates of early neuronal differentiation and axodendritic arborisation (46,47) . Another study demonstrated that D-gal affected inflammatory markers, such as iNOS, causing them to activate the NF-κB pathway (3) .…”
Section: Discussionmentioning
confidence: 96%
“…PYEDE treatment can effectively inhibit the activity of iNOS, reduce the content of NO and alleviate damage to the hippocampus and brain atrophy, possibly by renewing the ability of the brain to scavenge ROS (in vitro) and reducing lipid peroxidation and protein carbonylation. Previous studies have shown that inhibition of iNOS and NO generation can attenuate hippocampal neuronal apoptosis, and an ethanol extract of P. yezoensis promoted the development of hippocampal neurons by enhancing the rates of early neuronal differentiation and axodendritic arborisation (46,47) . Another study demonstrated that D-gal affected inflammatory markers, such as iNOS, causing them to activate the NF-κB pathway (3) .…”
Section: Discussionmentioning
confidence: 96%
“…Decreased plasma cholesterol levels in rats after the consumption of taurine were reported [56,61]. Promotion of neuronal development by taurine in laver extracts was also experimentally demonstrated by the primary culture of hippocampal neurons [76].…”
Section: Health Functionality Major Components Linked To Health Functmentioning
confidence: 94%
“…Anti-cancer polysaccharides (dietary fiber, porphyran), phospholipids, sterol, peptide [17,[46][47][48][49][50][51][52][53][54] Prevention of cardiovascular disease (e.g., hypertension, atherosclerosis, ischemia) betaine, dietary fiber, taurine, porphyran [17,[55][56][57][58][59][60][61] Antioxidant effect (e.g., Anti-ageing) porphyran, glycoprotein, polyphenols, tocopherols, peptide [62][63][64][65][66][67] Anti-inflammatory effect and immunomodulation glycoprotein, porphyran [64,[68][69][70][71][72][73] Alcohol metabolism glycoprotein [74,75] Prevention of nervous diseases (e.g., Alzheimer's diseases, methylmalonic acidemias) taurine, porphyran [38,76,77] Prevention of bone disease (e.g., osteoporosis, rheumatoid arthritis) porphyran, glycoprotein [64,78] Anti-diabetes mellitus phenolic compounds (carotenoids, anthocyanins), polysaccharides (porphyran), peptide [79][80][81][82] Porphyran is the distinctive dietary fiber found in laver, and its health effects were intensively studied to determine the nutritional/functional quality of ...…”
Section: Health Functionality Major Components Linked To Health Functmentioning
confidence: 99%
“…It has a backbone of alternating (1 → 4) -3,6-anhydro-α- L -galactopyranose units and (1 → 3) - linked β- D -galactose or (1 → 4)-linked α- L -galactose 6-sulfate units. In recent years, P. yezoensis polysaccharides have attracted attention as biomedical material because of their and antioxidants ( Zhao et al, 2006 ; Zhou et al, 2012 ), anticancer ( Yu et al, 2015 ), hypolipidemic ( Qian et al, 2014 ), immunoregulatory ( Zhang et al, 2003 ), the neurotrophic and neuroprotective activities ( Mohibbullah et al, 2015 ). Moreover, it has been demonstrated that polysaccharides carrageenans and their oligosaccharides can trigger defense systems against plant pathogens including bacteria, virus and fungi ( Stadnik and de Freitas, 2014 ).…”
Section: Introductionmentioning
confidence: 99%